De parientes, criados y gracias. Cultura del don y poder en el México colonial (siglos XVI-XVII) - Cañeque, Alejandro (2005)
Through an analysis of concepts such as liberality, magnificence, distributivejustice, gratitude and “beneméritos de Indias,” this article aims to examine theideological foundations of the culture of favor and reward which permeated all levels of colonial society in the sixteenth and seventeenth centuries. At the same time, this culture of favor and reward formed the basis for the relationships of patronage established by the Crown to provide cohesion to the Spanish empire. The Crown attempted to reproduce in Mexico and Peru the patronage system through the figure of the viceroy. However, the viceroys enjoyed sufficient autonomy to allow them to utilize the system on their own behalf, something which would be the source of great troubles for the Crown.